Factors Contributing to Organizational Job Stress among Dairy Scientists - A. Lalitha,; Ramkumar, (Journal of Agricultural Extension Management, 2025)
In the Indian Council of Agricultural Research system, all the scientists, irrespective of their specialization are expected to devote their time and efforts in certain domains like research, teaching and extension; and in each of these perspectives; they may undergo some job stress. This study was conducted to measure and compare the level of organizational job stress among dairy scientists and to find out the factors responsible for organizational job stress. A total of 120 scientists, with a minimum five years of job experience were purposively selected. The level _of stress was found moderate. Scientists were found to be having slightly more amount of stress than other categories. Personal and organizational factors were found to be most important factors contributing to job stress with 44.47 per cent variance. The factors yielded when regressed with job stress, accounted for 57.80 per cent variance. Only social factors showed a positive and significant relation with stress.